Peningkatan Kapasitas Penelitian Guru dan Siswa SMA Melalui Pelatihan Metodologi Penelitian dan Pendampingan Olimpiade Penelitian Siswa Indonesia - Andreas A. Sukmana; Sri Kasmiyati; Betty E. Kristiani; Hindriyanto D. Purnomo; Budhi Kristianto; Krismiyati Krismiyati; Teguh I. Bayu; Radius Tanone; Adi Nugroho; Hanita Yulia; Evangs Mailoa; Erwien Christianto (LPPM Uncen, 2026)
Critical and innovative thinking skills are essential requirements for students to meet the global challenges. One strategy to develop these skills is through participation in the Indonesian Student Research Olympiad (OPSI), which requires collaboration between teachers and students in implementing fundamental research concepts. However, the implementation of basic research concepts within the high school curriculum remains limited. Consequently, collaboration with higher education institutions serves as a potential solution, specifically through research training and mentoring. This training initiative aimed to enhance the research competence of teachers and students at SMAN 1 Ambarawa by providing methodology training and mentoring for OPSI research teams, conducted by a faculty team from Satya Wacana Christian University. The program was conducted intensively consisting of research design training and research mentoring for nine student groups. The training and the mentoring were provided by lecturers whose expertise aligned with the specific OPSI proposal topics of each group. This mentoring resulted in an overall improvement in the research capabilities of both teachers and students, with one group successfully won a gold medal at OPSI 2025. In conclusion, this program results in a positive reception, which expressed the hope that similar initiatives can be conducted on a regular basis.